2013
DOI: 10.1523/jneurosci.2331-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress Induces Schizophrenia-Like Alterations of Serotonin 2A and Metabotropic Glutamate 2 Receptors in the Adult Offspring: Role of Maternal Immune System

Abstract: It has been suggested that severe adverse life events during pregnancy increase the risk of schizophrenia in the offspring. The serotonin 5-HT2A and the metabotropic glutamate 2 (mGlu2) receptors both have been the target of considerable attention regarding schizophrenia and antipsychotic drug development. We tested the effects of maternal variable stress during pregnancy on expression and behavioral function of these two receptors in mice. Prenatal stress increased 5-HT2A and decreased mGlu2 expression in fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 78 publications
9
94
0
Order By: Relevance
“…Compared with controls, MIA offspring display an elevated level of 5-HT2AR in the PFC, which can explain the deficit of sensory gating and greater DOI-induced schizophrenia-like behavior and brain activity in these animals. Increased 5-HT2AR in the PFC was also reported for other rodent models that exhibit high sensitivity to DOI (29)(30)(31). Moreover, similar observations were made in antipsychotic-free schizophrenic subjects (28).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Compared with controls, MIA offspring display an elevated level of 5-HT2AR in the PFC, which can explain the deficit of sensory gating and greater DOI-induced schizophrenia-like behavior and brain activity in these animals. Increased 5-HT2AR in the PFC was also reported for other rodent models that exhibit high sensitivity to DOI (29)(30)(31). Moreover, similar observations were made in antipsychotic-free schizophrenic subjects (28).…”
Section: Discussionsupporting
confidence: 77%
“…Here, we combined these two factors, MIA and an acute injection of hallucinogenic drug DOI, and found that MIA offspring display stronger DOI-induced behavioral responses and greater brain activity as measured both by IEG induction and MEMRI. Elevated sensitivity to DOI and up-regulation of egr-1 in the PFC was also reported previously for offspring born to influenzainfected or poly(I:C)-injected pregnant mice (30,31). In addition, these mice also display a decreased density of metabotropic glutamate 2 receptors (mGluR2s) in the PFC.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, both male as well as female rats born to immune-challenged mothers showed a significantly stronger response compared to control animals. Similar findings have also been observed in adult mice exposed to prenatal stress as well as in offspring born to influenza virus infected mothers (Moreno et al, 2011;Holloway et al, 2013). Additionally, prenatally immune-challenged mice displayed an elevated DOI-induced neuronal activity in several brain regions, including the PFC, thalamus and striatum, as revealed by manganese-enhanced magnetic resonance imaging (Malkova et al, 2014).…”
Section: Doi-induced Head Twitch Behavior and Locomtor Activitysupporting
confidence: 74%
“…There is some evidence that prenatal stress alters maternal care, which might influence and further contribute to the alterations in the offspring (Francis et al, 1999;Kuo et al, 2014). Although in this experiment we were unable to dissect any contribution of prenatal and postnatal maternal effects on the programmed phenotypes in offspring, previous studies including in this model suggest that the programming effects induced by prenatal treatment are independent of maternal postnatal behavior (Holloway et al, 2013;Nyirenda et al, 2001). …”
Section: Discussionmentioning
confidence: 71%